Isolation of a DNA fragment that encodes part of an ATP dependent RNA helicase in Neurospora crassa. - I. E. Hunt; B. J. Bowman (Fungal Genetics Reports, 1997)
A DNA fragment encoding part of an ATP dependent RNA Helicase was isolated as part of a search for an unrelated gene. The sequence is reported here and homology to other related genes is described.